Production and characterisation of cold-bonded lightweight aggregates from biomass waste ash by cementing and one-part alkali-activation method / Lin Jiayi - Lin , Jiayi (2025)
Nowadays, increasing amounts of biomass ash are being sent to landfills, occupying substantial land space and causing health problems due to inadequate control measures. Rapid industrialization has also led to the over consumption of natural aggregates, creating environmental problems. Consequently, the production of artificial aggregates using biomass ash has gained considerable interest as it reduces the consumption of natural aggregates and landfill areas while recycling biomass ash. This study explored the feasibility of producing cold-bonded lightweight aggregates (CBLWA) using biomass ash, namely municipal woody biomass ash (MWBA) and palm oil fuel ash (POFA). First, the granulation parameters for MWBA-based cementing aggregate (MCA) were optimized. It was determined that an optimal water content of 27–29%, a rotation angle of 55° and a rotation speed of 60 rpm resulted in high granulation efficiency of 97.84%. The MCA exhibited a loose bulk density of 841 to 1058 kg/m3, a water absorption of 22 to 25% and a crushing strength of 2.2 to 2.6 MPa with 20% cement content. A low greenhouse gas emissions method for manufacturing another type of MWBA-based CBLWA, known as MWBA-based one-part alkali-activated aggregate (MAA), was also investigated. The MAA showed a loose bulk density, water absorption and crushing strength of 875–919 kg/m3, 11.2–13.8% and 1.7–2.3 MPa, respectively. With 15% Na2SiO3.5H2O, increasing GGBS content from 0 to 30% significantly enhanced crushing strength from 0.84 to 2.25 MPa and reduced water absorption from 24.0 to 12.5%. Secondly, the granulation parameters for POFA-based one-part alkali-activated aggregate (PAA) were optimized. Response surface methodology modeling revealed that the optimal rotation angle and speed for PAA manufacturing were 55° and 50 rpm, respectively, greatly improving the granulation efficiency of PAA from 79.9 to 88.2%. The PAA had a loose bulk density of 718.3 to 742.3 kg/m3 and crushing strength of 2.1 and 2.7 MPa. Thirdly, the characteristics of lightweight aggregate concretes (LWAC) made with these CBLWA were evaluated, obtaining an oven-dried density of 1682–1878 kg/m3 and 28 d compressive strength from 25.0 to 33.0 MPa. The MWBA-based alkali-activated aggregate concrete (MAAC) showed better high temperature resistance properties, with a 60% strength loss comparable to other LWAC. POFA-based alkali-activated aggregate concrete (PAAC) demonstrated a thermal conductivity value of 0.49 W/m·K per 1000 kg/m3, similar to other LWAC. Lastly, the environmental impacts of the produced CBLWA and LWAC were assessed using life-cycle assessment. MAA had the highest cumulative energy demand and global warming impact among CBLWA. PAAC, with the highest effective energy demand (232.4 MJ/MPa), was deemed less feasible with its current manufacturing method, while POFA-based cementing aggregate concrete (PCAC) recorded the lowest at 165 MJ/MPa. Leaching tests showed that the heavy metal concentrations in LWAC met multiple environmental safety standards, proving them safe for use. Overall, the study highlights the potential and environmental benefits of recycling MWBA and POFA into CBLWA and LWAC.